PENGARUH IMPULSE BUYING TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Mahasiswa Manajemen Bisnis Syariah STAIN Mandailing Natal) - Melda Junita Nst; Sari Fitri, Ade Khadijatul Z Hrp (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to determine the influence of impulse buying on purchasing decisions of STAIN Mandailing Natal students. This research was carried out at STAIN Mandailing Natal, Sharia Business Management study program, Jl. Prof. Dr. Andi Hakim Nst STAIN Pidoli Lombang Complex, Panyabungan District, Mandailing Natal Regency. Online impulse buying will occur in consumers who have spontaneous buying behavior which results in low self-control when receiving stimulation from online shopping sites. With the influence of impulse buying, it is hoped that students will not exceed reasonable limits when making online purchases. The purpose of this research is to determine the partial influence of impulse buying on purchasing decisions. The type of research used in this thesis is quantitative descriptive. The sample in this study was 75 respondents. The data collection technique used was observation and questionnaires using Google Form. The analysis method for this research uses validity tests, reliability tests, normality tests, heteroscedasticity tests, simple linear regression tests, partial tests and coefficient of determination tests. All of these tests were carried out using the SPSS version 25 program. Impulse Buying has a partial positive effect on the Purchasing Decisions of STAIN Mandailing Natal students as indicated by a significance value of t of 0.000 < 0.05, an R square value of 0.245, meaning that impulse buying is able to explain the dependent variable or purchasing decisions of 0.245 x 100% = 24.5% while 75 .5% is explained by other variables. Based on the research results, it can be concluded that impulse buying has a positive and significant influence on students' purchasing decisions with a calculated t value > t table (4.867 > 1.669).